The Effect of Analgesia with Ketamine, Morphine and Paracetamol for burn pain in north-eastern Iran - Mehrdad Mokarram; Alireza Sedaghat; Nasibeh Lotfalizadeh; Maliheh Ziaee; Negar Morrovatdar; Soheila Bicheranloee (Archives of Anesthesia and Critical Care, 2023)
Background: Pain is a common and challenging problem in burn patients. The severity of pain in these patients often requires multi drug therapy. On the other hand, with increasing the number and dosage of drugs, the complications increase, so finding an instruction that provides acceptable analgesia with minimal complications is necessary. Methods: Based on the dose and half-life, the initial dose for paracetamol was 15 mg/kg every 6 hours, this dose was reduced to 30% after three days of initiation of the treatment to prevent liver toxicity and was discontinued after one week. Morphine started with an initial dose of 0.01 mg/kg/h and for opioid-tolerant patients, the initial dose was 0.02 mg/kg/h. Morphine infusion dose raised by 30 percent every week. The continuous intravenous infusion of ketamine (0.15 mg/kg/hr) with continuous intravenous infusion of morphine was administered by a silicone pump. Results: The mean NRS was significantly reduced in the first visit after the intervention (three hours later) (8.5 ± 1.04 vs.3.9 ± 1.74; p <0.001) and this decrease was observed in NRS in continuous observations (P> 0.001). Pain reduction was independent of history of opioids use. Conclusion: Continuous infusion of ketamine, morphine and paracetamol showed an effective pain management program for burn patients.